OTU table of raw abundance - Galan, Maxime; Razzauti, Maria; Bard, Emilie; Bernard, Maria; Brouat, Carine; Charbonnel, Nathalie; Dehne-Garcia, Alexandre; Loiseau, Anne; Tatard, Caroline; Tamisier, Lucie; Vayssier-Taussat, Muriel; Vignes, Hélène; et al. (Dryad Digital Repository, 2016)
This XLSX file contains the number of reads obtained for the Operational Taxonomic Units (OTU ≥ 100 reads due to file size limits for Excel) of the two MiSeq runs and each PCR product before the data filtering.